Coating of upconversion nanoparticles with silica nanoshells of 5–250 nm thickness - Kembuan, Cynthia; Saleh, Maysoon; Rühle, Bastian; Resch-Genger, Ute; Graf, Christina (Beilstein Journal of Nanotechnology, 2019)
A concept for the growth of silica shells with a thickness of 5–250 nm onto oleate-coated NaYF4:Yb3+/Er3+ upconversion nanoparticles (UCNP) is presented. The concept enables the precise adjustment of shell thicknesses for the preparation of thick-shelled nanoparticles for applications in plasmonics and sensing. First, an initial 5–11 nm thick shell is grown onto the UCNPs in a reverse microemulsion. This is followed by a stepwise growth of these particles without a purification step, where in each step equal volumes of tetraethyl orthosilicate and ammonia water are added, while the volumes of cyclohexane and the surfactant Igepal® CO-520 are increased so that the ammonia water and surfactant concentrations remain constant. Hence, the number of micelles stays constant, and their size is increased to accommodate the growing core–shell particles. Consequently, the formation of core-free silica particles is suppressed. When the negative zeta potential of the particles, which continuously decreased during the stepwise growth, falls below −40 mV, the particles can be dispersed in an ammoniacal ethanol solution and grown further by the continuous addition of tetraethyl orthosilicate to a diameter larger than 500 nm. Due to the high colloidal stability, a coalescence of the particles can be suppressed, and single-core particles are obtained. This strategy can be easily transferred to other nanomaterials for the design of plasmonic nanoconstructs and sensor systems.
Keywords: reverse microemulsion; silica coating; stepwise growth; thick shells; upconversion nanoparticles